2004
DOI: 10.1128/mcb.24.17.7779-7794.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Jun Blockade of Erythropoiesis: Role for Repression of GATA-1 by HERP2

Abstract: Although Jun upregulation and activation have been established as critical to oncogenesis, the relevant downstream pathways remain incompletely characterized. In this study, we found that c-Jun blocks erythroid differentiation in primary human hematopoietic progenitors and, correspondingly, that Jun factors block transcriptional activation by GATA-1, the central regulator of erythroid differentiation. Mutagenesis of c-Jun suggested that its repression of GATA-1 occurs through a transcriptional mechanism involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 78 publications
2
59
0
Order By: Relevance
“…In addition, 57% Ϯ 3% of miRNA-155-transduced K562 cells expressed CD41 (mean fluorescence intensity (MFI) ϭ 11.5 Ϯ 1.2), in comparison with 78 Ϯ5% of control K562 cells (MFI ϭ 32.8 Ϯ 3.5) treated with IDB-expressed CD41 (data not shown). Both the decrease in percentage of cells positive for CD41, as well as the Ϸ3-fold decrease in MFI, are indicative of a large decrease in K562 cell megakaryocytic differentiation (13)(14)(15). K562 cells transduced with miRNA-155 proliferated at a similar rate to those transduced with control vector (data not shown), indicating that the observed lack of differentiation was not due to cell cycle arrest or decreased cell growth rate.…”
Section: He-mirnas Regulate Hematopoietic Differentiation-associatedmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, 57% Ϯ 3% of miRNA-155-transduced K562 cells expressed CD41 (mean fluorescence intensity (MFI) ϭ 11.5 Ϯ 1.2), in comparison with 78 Ϯ5% of control K562 cells (MFI ϭ 32.8 Ϯ 3.5) treated with IDB-expressed CD41 (data not shown). Both the decrease in percentage of cells positive for CD41, as well as the Ϸ3-fold decrease in MFI, are indicative of a large decrease in K562 cell megakaryocytic differentiation (13)(14)(15). K562 cells transduced with miRNA-155 proliferated at a similar rate to those transduced with control vector (data not shown), indicating that the observed lack of differentiation was not due to cell cycle arrest or decreased cell growth rate.…”
Section: He-mirnas Regulate Hematopoietic Differentiation-associatedmentioning
confidence: 89%
“…Cells then were washed with PBS and cultured in complete growth media containing ingenol 3,20-dibenzoate (IDB, 1 g/ml; Sigma) or hemin (50 M; Sigma). On day 4, IDB-treated cells were assayed by monoclonal antibody staining and flow cytometry for CD41 (Becton Dickinson, Franklin Lake, NJ) expression, indicating megakaryocytic differentiation (13)(14)(15). Hemin-treated cells were assayed similarly on day 6 for benzidine staining, indicating erythroid differentiation (33).…”
Section: Associated Mrnas Expressed In Hspcsmentioning
confidence: 99%
“…How this occurs is a matter of speculation. Hey proteins have been shown to bind histone deacetylases in vitro (14), but many studies have indicated Hey-mediated repression is insensitive to trichostatin A (18,19,21,28), calling into question the rele-3 M. F. Buas, S. Kabak, and T. Kadesch, unpublished observations. vance of such associations.…”
Section: Discussionmentioning
confidence: 99%
“…Hey1 has been shown to bind GATA1 and neutralize its ability to induce erythropoiesis (18), whereas all three Hey family members are capable of binding to GATA4/6 and inhibiting GATA-driven cardiac gene expression (19,20). Inhibitory physical interactions between Hey proteins and Runx2 may prevent Runx-induced aortic calcification (21), whereas associations between Hey factors and Ptf1-p48 may account for Notch-directed inhibition of pancreatic exocrine differentiation (22).…”
mentioning
confidence: 99%
“…NACA is also known as a coactivator of c-JUN-mediated transcription in developing bone during embryogenesis Quelo et al, 2002). However, because c-JUN behaves as a negative regulator of erythropoiesis (Elagib et al, 2004), the positive effect of NACA on erythroid-cell maturation cannot be explained by its c-JUN-mediated positive contribution. Intriguingly, a recent study reports the positive effect of the c-JUN co-activator RNA helicase RHII/Guα through its association with MafK and other transcription factors that are essential for erythroid-cell-specific transcription (Brand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%